MODEL PENGEMBANGAN KURIKULUM TYLER DAN IMPLIKASINYA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Tatang Hidayat; Endis Firdaus; Momod Abdul Somad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The purpose of this present study is to identify the Tyler curriculum development model and its implications in learning Islamic Religious Education in school. This study employed a qualitative approach and literature study method. The results of this study showed that the conditions as the time progresses undeniably were in demands of curriculum development. The Tyler curriculum model had its own strengths and weaknesses. In fact, the model only emphasized the aspect of objectives, regardless of the ongoing educational process. Therefore, as an implication, it is obvious that the Tyler curriculum development model needed to be developed and it in fact should be viewed from various aspects, especially with regard to Islamic Religious Education which had its own distinguishing characteristics in establishing the values of faith, piety, and noble character. Therefore, Islamic Religious Education teaching and learning processes undeniably should focus on the ongoing educational processes, not merely to the evaluation held at the end of the learning process.